HPLC/DAD-MS CHARACTERISATION OF DIVERSE DYESTUFFS FROM A CASE STUDY OF HISTORIC FABRIC - YURDUN, TÜRKAN (UNIV AGEAN, DEPT MEDITERRANEAN STUD, 2018)
Unknown dyestuffs from a red crimson coloured historic fabric are analysed with both High Performance Liquid Chromatography (HPLC) coupled with Diode Array Detection (DAD) and Liquid Chromotography coupled with Mass Spectrometry(LC-MS.) The dyed fabric dates back to 18th -19th centuries AD and is located in the National Museum of Beit El Omma in Egypt. the lengthwise and crosswise yarns have different colours, thus different dyes are anticipated. Chromatographic separation of the hydrolysed samples of the lengthwise and crosswise yarns is performed with H2O: MeOH: 37% HCl (1:1:2; v/v/v; 400 mu L) using a gradient elution program of HPLC/DAD with two solvents. HPLC/DAD analysis results prove that the green dye of the lengthwise yarn originates from tannin and Gallic acid from rich natural resource ie., Gall oak or Walloon oak. Meanwhile, the red dye of the crosswise yarns is produced from a synthesised material, known as Orange II (acid orange 7). LC-MS is used to analyse the same dyes samples using Electrospray Ionisation Interface (ESI) ion source operating in negative mode to confirm the given results. This remarkable combination of natural and synthetic dyes on the same fabric is rarely encountered.
Keywords: Synthetic; natural; Chromatography; Crimson; Tannin; Orange II; dyes; LIQUID-CHROMATOGRAPHY; DYES; TEXTILES; IDENTIFICATION